At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Erik used the Factor Theorem to find the remainder of 2x3-4x2-28x+6 divided by x+3. If he calculated the remainder to be 0, what does that tell him?

Sagot :

Step-by-step explanation:

x + 3 = 0

x = - 3

f(x) = 2x³ - 4x² - 28x + 6

f(- 3) = 2(- 3)³ - 4(- 3)² - 28 x (- 3) + 6

= 2 x (- 27) - (4 x 9) + 84 + 6

= - 54 - 36 + 90

= - 90 + 90

= 0

Therefore,

x + 3 is factor of 2x³ - 4x² - 28x + 6